Crystal structure of ArOYE6 reveals a novel C‐terminal helical extension and mechanistic insights into the distinct class III OYEs from pathogenic fungi. (29th March 2022) - Singh, Yeshveer; Sharma, Ruby; Mishra, Manasi; Verma, Praveen Kumar; Saxena, Ajay Kumar
Abstract : Old yellow enzymes (OYEs) play a critical role in antioxidation, detoxification and ergot alkaloid biosynthesis processes in various organisms. The yeast‐ and bacteria‐like OYEs have been structurally characterized earlier, however, filamentous fungal pathogens possess a novel OYE class, that is, class III, whose biochemical and structural intricacies remain unexplored to date. Here, we present the 1.6 Å X‐ray structure of a class III member, OYE 6 from necrotrophic fungus Ascochyta rabiei (ArOYE6), in flavin mononucleotide (FMN)‐bound form (PDB ID‐7FEV ) and provide mechanistic insights into their catalytic capability. We demonstrate that ArOYE6 exists as a monomer in solution, forms (β/α)8 barrel structure harbouring non‐covalently bound FMN at cofactor binding site, and utilizes reduced nicotinamide adenine dinucleotide phosphate as its preferred reductant. The large hydrophobic cavity situated above FMN, specifically accommodates 12‐oxo‐phytodienoic acid and N ‐ethylmaleimide substrates as observed in ArOYE6‐FMN‐substrate ternary complex models. Site‐directed mutations in the conserved catalytic (His196, His199 and Tyr201) and FMN‐binding (Lys249 and Arg348) residues render the enzyme inactive. Intriguingly, the ArOYE6 structure contains a novel C‐terminus (369–445 residues) made of three α‐helices, which stabilizes the FMN binding pocket as its mutation/truncation lead to complete loss of FMN binding. Moreover, the loss of the extended C‐terminus does not alter the monomeric nature of ArOYE6. In this study, for the first time, we provide the structural and biochemical insights for a fungi‐specific class III OYE homologue and dissect the oxidoreductase mechanism. Our findings hold broad biological significance during host–fungus interactions owing to the conservation of this class among pathogenic fungi, and would have potential implications in the pharmacochemical industry. Abstract : Old yellow enzymes have a range of physiological functions in various organisms. In this study, Yeshveer Singh and co‐authors determine the first high resolution (1.6 Å) crystal structure of ArOYE6, a novel, fungi‐specific class III old yellow enzyme from a necrotrophic pathogen, Ascochyta rabiei . The authors demonstrate that the ArOYE6 monomer folds into a (β/α)8–barrel, contains a novel C‐terminal extension made of three additional α‐helices, and accommodates flavin mononucleotide (FMN) in the co‐factor binding site via non‐covalent interactions. Moreover, they dissect the mechanism of substrate reduction by ArOYE6. A Commentary in this issue further highlights the broad significance of this study.